Prevalence of Hepatitis-B and Hepatitis-C viruses among HIV infected subjects attending Wad Medani VCT/ART centre, Gezira State, Sudan - Mohammed, Moawia Elbalal; Elawad, zzaddinn; Gasmelseed, Nagla (Gezira Journal of Health Sciences; Vol 8 No 1 (2012), 2012)
Objectives: This is a descriptive, prospective, cross-sectional, hospital based study to determine the prevalence of Hepatitis B Virus and Hepatitis C Virus among Human Immunity deficiency Virus infected subjects in the Gezira State of central Sudan. Materials and Methods : The study was carried out on HIV infected subjects attending Wad Medani VCT/ART centre from Dec. 2010 to March 2011. Epidemiological and demographic characteristics were recorded and participants were interviewed for risk factors of viral hepatitis infection. Blood samples were then collected and tested for HBsAg and HCV antibodies. Results : A total of 50 subjects were screened with a mean age of 36.39±13.57, 52% were males, HBsAg and HCV antibodies were reactive in 8% and 0% (none) of the studied group, respectively. Conclusion : This study shows that the prevalence of HBV/HIV co-infection is consistent with both regional and global rates, while HCV/HIV co-infection is low in the studied group. ملخص: الأهداف: تحديد شيوع الإصابة بالتهاب الكبد الحموى ب (HBV) و ج (HCV) وسط المرضى المصابين بحمى عوز المناعة المكتسب (HIV  ) بولاية الجزيرة وسط السودان. المرضى و الوسائل: هذه دراسة وصفية توقعية مقطعية مبنية على المستشفى. أجريت الدراسة في المرضى المصابين بحمى عوز المناعة المكتسب المترددين على مستشفى ودمدني مركز ART/VCT في الفترة بين ديسمبر 2010م و حتى مارس 2011م الميزات الوبائية والملامح السكانية رصدت و تمت معاينة المشاركين لمعرفة عوامل الخطورة للإصابة بحمى الكبد. جمعت عينات الدم و تم فحصها للمضاد المناعي HBsAg و مضاد حمى ج HCV . النتائج:   مجموع 50 حالة تم مسحها بمتوسط عمر 36.39 ± 13.57  . نسبة ذكور كانت 52% من الحالات. مضادات HBsAg  وHCV   كانت متفاعلة في 8% و 0% (لا يوجد) على التوالي. الخلاصة: أوضحت الدراسة شيوع الاصابة بالتهاب الكبد الحموى ب HBV وسط المصابين HIV تتماشى مع معدلات شيوع الإصابة الإقليمية و العالمية . بينما الاصابه الحمى الكبدي ج (HCV) كان ضعيف فى المجموعه المدروسة.